A pilot study of patient satisfaction with a self-completed tablet-based digital questionnaire for collecting the patient’s medical history in an emergency department - Leander Melms; Juergen R. Schaefer; Andreas Jerrentrup; Tobias Mueller (BMC Health Services Research, 2021)
Abstract Background The increasing popularity and availability of tablet computers raises questions regarding clinical scenarios. This pilot study examined the patient’s satisfaction when using a tablet-based digital questionnaire as a tool for obtaining medical history in an emergency department and to what extent gender, age, technical competence and mother tongue influence the user satisfaction. Patients were asked to complete three consecutive questionnaires: The first questionnaire collected basic epidemiological data to measure past digital usage behaviour, the second questionnaire collected the patient’s medical history, and the third questionnaire assessed the overall perceived user satisfaction when using the tablet-based survey application for medical anamnesis. Results Of 111 consenting patients, 86 completed all three questionnaires. In summary, the user evaluation was positive with 97.7% (n = 84) of the patients stating that they had no major difficulties using the digital questionnaire. Only 8.1% (n = 7) of patients reported a preference to fill out a paper-and-pen version on the next visit instead, while 98.8% (n = 85) stated that they would feel confident filling out a digital questionnaire on the next visit. The variables gender, age, mother tongue and/or technical competence did not exert a statistically significant influence towards the defined scales usability, content and overall impression. Conclusion In conclusion, self-administered tablet-based questionnaires are widely accepted tools for collecting medical information in the emergency room across all ages and genders, regardless of technical competence.